2004
DOI: 10.1007/s00226-004-0250-8
|View full text |Cite
|
Sign up to set email alerts
|

Decay resistance against Coriolus versicolor in Sessile oak ( Quercus petraea Liebl.): analysis of the between-tree variability and correlations with extractives, tree growth and other basic wood properties

Abstract: Weight loss due to fungus Coriolus versicolor has been measured on 614 samples according to the NF EN 113 norm. Up to eight samples were cut at breast height (two opposite radii·four radial positions in heartwood) from 82 mature sessile oaks (Quercus petraea Liebl.) originating from contrasting regions, silvicultural schedules and site qualities in France. The following points are addressed in the paper: (i) contribution to the total variability for weight loss of the effects ''tree'', ''position in the tree''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 5 publications
2
20
0
5
Order By: Relevance
“…The significant tree effect on decay could be partially explained by the age difference among trees from a same site. This result is in good agreement with previous findings (Guilley et al 2004;Windeisen et al 2002). Moreover, several studies have attributed a significant tree effect on decay to the difference in extractives content between trees, which is age dependent (Anagnost and Smith 1997;Oliveira et al 2010;Windeisen et al 2002).…”
Section: Variations In Sapwood Heartwood and Decaysupporting
confidence: 92%
“…The significant tree effect on decay could be partially explained by the age difference among trees from a same site. This result is in good agreement with previous findings (Guilley et al 2004;Windeisen et al 2002). Moreover, several studies have attributed a significant tree effect on decay to the difference in extractives content between trees, which is age dependent (Anagnost and Smith 1997;Oliveira et al 2010;Windeisen et al 2002).…”
Section: Variations In Sapwood Heartwood and Decaysupporting
confidence: 92%
“…Previous studies with other species such as Cinnamomum camphora (Hashimoto et al, 1997) showed that variation in termite resistance could be explained by the concentration of the largely responsible component (camphor). Significant correlations were reported between ellagitannin content and decay resistance of Quercus petraea (Guilley et al, 2004), whereas the variation in decay resistance of Larix sibrica (Venalainen et al, 2006) showed a good correlation with taxifolin content. In contrast, Taylor et al (2006) found that variations in extractive components explained relatively little the variation in fungal and termite resistance of Thuja plicata and Chamaecyparis nootkanensis wood.…”
Section: Relationship Between Extractive Compounds and Natural Termitmentioning
confidence: 99%
“…Several studies have dealt with the distribution of extractive components in other species. The decrease in some active component contents in inner heartwood was noted in Thuja plicata (Nault, 1988), Pinus sylvestris (Venalainen et al, 2003) and Quercus petraea (Guilley et al, 2004).…”
Section: Compound Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural decay resistance of wood is dependant on the amount and quality of primary metabolites and on the storage of extractives deposited in the heartwood (Delaveau and Vidal-Tessier, 1988;Zabel and Morell, 1992). These substances inhibit the primary metabolism of fungi or the degradation process that they trigger, and their content increases with the tree age (Hillis, 1987;Nault, 1988;Posey and Robinson, 1969 (Gartner et al, 1999, Guilley et al, 2004. Decay variations were due to the presence of extractives formed between the sapwood and the outermost, to the duraminisation and ageing process.…”
Section: Decay Resistance Measurementsmentioning
confidence: 99%